PENERAPAN MODEL PEMBELAJARAN PETA KONSEP UNTUK MENINGKATKAN HASIL BELAJAR IPA KELAS IV SDN 016 TALANG PRING JAYA KECAMATAN RAKIT KULIM KABUPATEN INDRAGIRI HULU - Rohani Rohani; Gustimal Witri; Hendri Mahardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to improve learning outcomes IPA of class IV Elementary School 016 Talang Pring Jaya in the academic year 2014/2015. This study is a Class Action Research (Classroom Actions Research), which consists of four stages: planning, action, observation, and reflection. Subjects in this class IV Elementary School 016 Talang Pring Jaya as many as 20 students. Based on the results of research and data analysis known that an increase in the percentage of teachers in the first cycle of activity by 70% with sufficient qualifications, increased in the second cycle to 92.5% with excellent qualifications. There is a difference between an increase of 22.5%. The percentage of student activity in the first cycle of 62.5% with sufficient qualifications, increased in the second cycle to 92.5% with excellent qualifications. There is a difference between a 30% increase. In addition, improving student learning outcomes by using a learning model concept maps are a base score (57.75), UH 1 (70.75), UH 3 (88). With the number of students who completed prior to the implementation of the learning model concept maps are 9 people (45%). And after application of learning models of concept maps, one cycle increased to 10 people (50%), and the second cycle increased again to all students 20 people (100%). For that reason, it can be concluded that the application of the learning model concept maps can enhance student learning outcomes of class IV Elementary School 016 Talang Pring Jaya.Keywords : Learning Model Concept Maps, IPA Learning Outcomes